NAVIGATING THE NEW NORMAL: A PRACTICAL GUIDE TO POST-PANDEMIC HR POLICIES - Tuti Damayanti; Ramon Zamora; Lukmanul Hakim (RADJA PUBLIKA, 2026)
The COVID-19 pandemic precipitated a permanent transformation in the global workplace, shifting employee expectations toward flexibility, well-being, and purpose. This has created a critical misalignment with traditional, office-centric HR policies, leading to risks of attrition, inequity, and disengagement. This article aims to develop a practical framework for redesigning HR policies to meet the demands of the post-pandemic